Pengaruh Potongan Harga E-Ticketing dan Attractiveness terhadap Keputusan Pengunjung Wisata Dunia Fantasi pada Event Tertentu sebagai Pemoderasi - Yani, Ari Soeti; Setyaningsih, Putri (Jurnal Samudra Ekonomi dan Bisnis, 2024)
The research aims to test whether e-ticketing discounts and attractiveness are related to visitors' decisions on the Dunia Fantasi tour at certain events as moderators. This research is motivated by the phenomenon of increasing use of electronic services in Indonesia and becoming an attraction in the millennial era of customers. The data analysis process uses the SmartPLS application as data processing using a sample of 155 participants. The analysis stages include participant demographic data, statistics of variable descriptive, validity and reliability testing, and hypothesis testing. The results show that there is a positive and significant influence from e-ticketing discounts, attractiveness and certain event programs on visitors’ decisions to visit Dunia Fantasi tourism. Furthermore, the moderating role of certain event programs is significant in the influence of e-ticketing prices or attractiveness on the visitors’ decisions of Dunia Fantasi tourism.